FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Fella Resty Rakhmadani, 14.05.52.0259; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of liquidity, leverage, growth, institutional ownership, and profitability on dividend policy in manufacturing companies listed on the Stock Exchange for the years 2015-2017. The research sample was obtained using purposive sampling method. Based on several predetermined criteria, there were 129 companies which were the research samples. The data analysis technique used in this study is multiple linear regression. Based on the results of data analysis, liquidity variables have a negative effect not significantly on dividend policy, Leverage has no significant positive effect on dividend policy, Growth has no significant negative effect on dividend policy, Institutional ownership has a significant negative effect on policy, and profitability variables have a significant positive effect on policy dividend.